2011
DOI: 10.1007/s00441-011-1274-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of TGF-β in the pathogenesis of primary open-angle glaucoma

Abstract: Transforming growth factor-β2 (TGF-β2) is found in increasing amounts in aqueous humor and reactive optic nerve astrocytes of patients with primary open-angle glaucoma (POAG), a major cause of blindness worldwide. The available data strongly indicate that TGF-β2 is a key player contributing to the structural changes in the extracellular matrix (ECM) of the trabecular meshwork and optic nerve head as characteristically seen in POAG. The changes involve an induction in the expression of various ECM molecules and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
224
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(239 citation statements)
references
References 153 publications
3
224
0
5
Order By: Relevance
“…However, the main source of TGFB2 in AH is either the epithelial layer of the ciliary body (28) or the lens (29). Previous studies have shown that TGFB2 affected the trabecular meshwork, which is an important tissue for draining AH and maintaining normal IOP (30). As complex changes in the trabecular meshwork gradually affect its ability to drain AH from the anterior chamber, it can lead to elevated IOP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main source of TGFB2 in AH is either the epithelial layer of the ciliary body (28) or the lens (29). Previous studies have shown that TGFB2 affected the trabecular meshwork, which is an important tissue for draining AH and maintaining normal IOP (30). As complex changes in the trabecular meshwork gradually affect its ability to drain AH from the anterior chamber, it can lead to elevated IOP.…”
Section: Discussionmentioning
confidence: 99%
“…According to the pathway modeling, RhoA signaling, the central pathway that regulates the actin cytoskeleton of the TM, is initiated by exposure to pigment via a complex consisting of insulin growth factor (IGF), the type 1 insulin-like growth factor receptor (IGF-IR), and the lysophosphatidic acid receptor (LPAR) in the cell membrane. This is different from the RhoA activation induced by transforming growth factor (TGF)-β and its receptor in primary open-angle glaucoma 69 and steroid glaucoma 70 . In addition to the inhibition of tight junctions by RhoA, upregulation of the rhophilin Rho GTPase binding protein would also promote reorganizing the TM actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 81%
“…TGF-b I and TGF-b II appear to have important roles in optic nerve degeneration (Zode et al 2009;Fuchshofer 2011) as well as trabecular meshwork function (Sethi et al 2011;Fuchshofer 2012). LTPB2 (associated with congenital glaucoma and anterior segment dysgenesis) and CDKN2BAS (associated with POAG, NTG) are part of the overall TGF-b signaling pathway.…”
Section: Transforming Growth Factor B (Tgf-b) Signalingmentioning
confidence: 99%